KUR Credit Scoring Assessment for Prospective Debtors to Minimize Non Performing Loan at BPD Sumsel Babel Main Branch Kapten A.Rivai - Divaputri, Adelya; Panuntun, Bagus (Publikasi Inspirasi Indonesia, 2024)
This research entitled “KUR Credit Scoring Assessment for Prospective Debtors to Minimize Non Performing Loan at BPD Sumsel Babel Main Branch Kapten A.Rivai” analyze the credit assessment process that occurs in BPD Sumsel Babel. BPD Sumsel Babel is one of the financial institutions in Indonesia that supports economic growth in South Sumatera and Bangka Belitung. The main focus of this research is to identify obstacles in credit assessment related to KUR financing using descriptive qualitative research methods in the form observation, interviews, and documentation and also formulating recommendations that can improve the assessment for prospective debtors in order to prevent non performing loans in the future. Recommendations for BPD Sumsel Babel main branch Kapten A.Rivai in the form of improving the assessment form by adding question point to the credit analysis worksheet to develop a system in the form of an integrated website/platform.